Job Satisfaction among Medical Officers in a University Hospital: A Qualitative Study - Muhammad, Juliawati; Miswan, Natasha; Idris, Nur Suhaila; Muhamad, Rosediani (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Job satisfaction among medical officers (MOs) in university hospitals is crucial for both healthcare delivery and medical education. High job satisfaction is linked to improved productivity and mental well-being, while dissatisfaction can lead to errors, lower patient satisfaction, and higher employee turnover. Although many studies have examined job satisfaction in Malaysian healthcare settings, most have focused on public hospitals. This qualitative study aimed to explore the experiences of MOs actively working in a Malaysian university hospital to gain a better understanding into the factors influencing their job satisfaction. MATERIALS & METHODS: Using a phenomenological approach, 18 MOs were interviewed through semi-structured, in-depth interviews. The interviews were audio-recorded, transcribed verbatim, and analysed using thematic analysis. Guided by Herzberg’s Two-Factor Theory, we explored motivators and dissatisfiers in the MOs' work environment. RESULTS: Four main themes emerged: (1) enjoyment in patient care including aspects of diagnosing, treating, and communicating with patients, (2) personal fulfilment in relations to family time and educational responsibilities, (3) positive work culture comprising of teamwork and hospital facilities, and (4) distress related to hospital systems, salary, and career advancement. CONCLUSION: This study elucidated how different factors contribute to job satisfaction and dissatisfaction among service and postgraduate MOs. These findings underscore the need for targeted strategies by hospital management and policymakers to address these dynamics, in order to sustain a motivated medical workforce in university hospitals.